Accounting for central neighborhood change, 1980-2010 - Nathaniel Baum-Snow; Daniel Hartley (Federal Reserve Bank of Chicago, 2016)
Neighborhoods within 2 km of most central business districts of U.S. metropolitan areas experienced population declines from 1980 to 2000 but have rebounded markedly since 2000 at greater pace than would be expected from simple mean reversion. Statistical decompositions reveal that 1980-2000 departures of residents without a college degree (of all races) generated most of the declines while the return of college educated whites and the stabilization of neighborhood choices by less educated whites promoted most of the post-2000 rebound. The rise of childless households and the increase in the share of the population with a college degree, conditional on race, also promoted 1980-2010 increases in central area population and educational composition of residents, respectively. Estimation of a neighborhood choice model shows that changes in choices to live in central neighborhoods primarily reflect a shifting balance between rising home prices and valuations of local amenities, though 1980-2000 central area population declines also reflect deteriorating nearby labor market opportunities for low skilled whites. Rising 1980-2000 central neighborhood home prices were about equally offset by rising amenity valuations among college educated whites; declining amenity valuations reinforced rising home prices to incentivize departures of other demographic groups from central neighborhoods during this period. Greater increases in amenity valuations after 2000 encouraged college educated whites to move in and other whites to remain but were not large enough to offset rising housing costs for minorities.
Keywords: 330